Qinhuo Shanggan oral solution resolves acute lung injury by down-regulating TLR4/NF-κB signaling cascade and inhibiting NLRP3 inflammasome activation - Tang, Shun; Liang, Yuanjing; Wang, Minmin; Lei, Jiarong; Peng, Yuhui; Tao, Qiu; Ming, Tianqi; Yang, Wenyu; Zhang, Chuantao; Guo, Jinlin; Xu, Haibo (Frontiers in Immunology, 2023)
Acute lung injury (ALI) is a common condition, particularly in the COVID-19 pandemic, which is distinguished by sudden onset of respiratory insufficiency with tachypnea, oxygen-refractory cyanosis, reduced lung compliance and diffuse infiltration of pulmonary alveoli. It is well-established that increasing activity of toll-like receptor 4 (TLR4) / nuclear factor kappa-B (NF-κB) signaling axis and the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome activation are associated with the pathogenesis of ALI. Since ALI poses a huge challenge to human health, it is urgent to tackle this affliction with therapeutic intervention. Qinhuo Shanggan oral solution (QHSG), a traditional Chinese herbal formula, is clinically used for effective medication of various lung diseases including ALI, with the action mechanism obscure. In the present study, with the rat model of lipopolysaccharide (LPS)-induced ALI, QHSG was unveiled to ameliorate ALI by alleviating the pathological features, reversing the alteration in white blood cell profile and impeding the production of inflammatory cytokines through down-regulation of TLR4/NF-κB signaling cascade and inhibition of NLRP3 inflammasome activation. In LPS-stimulated RAW264.7 mouse macrophages, QHSG was discovered to hinder the generation of inflammatory cytokines by lessening TLR4/NF-κB signaling pathway activity and weakening NLRP3 inflammasome activation. Taken together, QHSG may resolve acute lung injury, attributed to its anti-inflammation and immunoregulation by attenuation of TLR4/NF-κB signaling cascade and inhibition of NLRP3 inflammasome activation. Our findings provide a novel insight into the action mechanism of QHSG and lay a mechanistic foundation for therapeutic intervention in acute lung injury with QHSG in clinical practice.